Behavioral intentions toward air purifier adoption in Thai municipal offices for sustainable indoor air quality - Amirhossein Taghipour; Amnuay Saengnoree; Assoc. Prof. Dr. Woranat Sangmanee (Discover Sustainability, 2025)
As outdoor air pollution in Thailand increases and indoor environments begin to trap the accumulation of fine particulate matter (PM 2. 5) outside and produce it inside, the protection of indoor air quality (IAQ) in municipal offices is an issue of public-health concern. In this paper, we test determinants of the behavioral intention to use (BIU) portable air purifiers in municipal executives by combining the theory of planned behavior (TPB) and technology acceptance model (TAM) with a structural equation modelling (SEM) model based on a survey of n = 320 municipal executives across the country. Findings reveal that the perceived innovativeness and effectiveness of air purifiers, as a constitute of a key antecedent of adoption, has positive and significantly large standardized path coefficients both directly affecting BIU and indirectly, through perceived behavioral control (PBC) and perceived ease of use (PEOU). Results also indicate that BIU is related to environmental air characteristics (EAC) in the perception of executives regarding ambient and indoor air conditions and that this influences adoption through PBC and, indirectly through performance expectancy (PE) (all significant paths p < 0.001). Collectively, the evidence cannot cause an effect but indicates strong in-direct pathways that can be used to support an explanation of technology acceptance in the workplaces of the public sector. The findings highlight the significance of the user-centered design, the ability to build capabilities, as well as to communicate the air-purifier performance in a clear way helping to improve perceived control and expectancy. This research can inform policy-makers with respect to ad-ministration of cities because it connects the concepts of IAQ management, occupational health, and sustainable procurement and emphasizes how convenient data dashboards and online visualizations of air quality can shape the willingness of executives to implement air purifying technologies.
Keywords: Indoor Air Quality and Microbial Exposure; Air Quality and Health Impacts; Air Quality Monitoring and Forecasting